Contextual Teaching and Learning in Elementary Mathematics Education: A Bibliometric Performance Analysis - Indry Wenno; Sofyan Iskandar; Prihantini Prihantini; Indry Wenno; Sofyan Iskandar; Prihantini (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Research on Contextual Teaching and Learning (CTL) in elementary mathematics education has expanded substantially over the past decade, yet no bibliometric study has systematically mapped its intellectual structure, growth pattern, or geographic distribution. This study addresses that gap through a bibliometric performance analysis of 55 Scopus-indexed documents published between 2009 and 2026, guided by three research questions on publication trends, geographic contributions, and source characteristics. Data were retrieved from the Scopus database on May 2, 2026, and analyzed using the Scopus Analyze Search Results feature and Microsoft Excel. Results reveal that annual output grew from one document in 2009 to a peak of 11 in 2020 (20.0% of total), declined to two in 2022 amid COVID-19 disruptions, and resurged to 10 in 2025, the second highest on record. Geographically, Indonesia accounts for 85.5% of publications (n = 47), followed by Malaysia (5.5%; n = 3), while contributions from Western countries and other regions remain negligible. Publication sources are dominated by conference proceedings: the Journal of Physics: Conference Series (36.4%) and AIP Conference Proceedings (20.0%) together account for 56.4% of all documents. These findings highlight the need for broader international collaboration, stronger journal-based dissemination, and expanded use of advanced bibliometric tools.